PENGARUH ROA, ROE, LDR, CR, DAN NPL TERHADAP KONDISI FINANCIAL DISTRESS PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2019-2022” - Ginting, Natalia Agrina Br; Munthe, Kornel; Purba, Antonius M (KUKIMA : Kumpulan Karya Ilmiah Manajemen, 2024)
The study aims to predict financial distress through the financial ratio variables Return on Asset, Return On Equity, Loan to Deposit Ratio, Current Ratio, and Non-Performing Loan, from one, two and three years before occurring in banking companies listed on the Indonesian Stock Exchange. The population in this study is 47 banking companies. Sampling techniques are purposive sampling according to certain criteria so that 35 samples are obtained from the company. Data obtained from the Indonesian Stock Exchange for the years 2019-2022. The data analysis technique used in this study is logistic regression analysis. The results of the research show that the return on asset, return on equity, Loan to Deposit Ratio, Current ratio, and Non-Performing Loan, together, significantly influenced the probability of financial distress in banking companies listed on the Indonesian Stock Exchange for one, two and three years before it occurred. The degree of accuracy of the prediction of the influence of the financial variable ratio on the probability of financial distress for one, two and three years before having suffered financial distresses was 88.6 per cent, 88.6, and 82.9 per cent. The test results partially showed that the Return on Asset from the first, second and third years before the financial distress has a positive and non-significant effect on the likelihood of financial distress, the Return on Equity from one, two and three years before the financial distress had a negative and significant impact on the probability of the financial distress, the Loan to Deposit Ratio from one, two and three years before the financial distress had a negative and significant impact on the probability of the financial distress, the Ratio of Current Ratio from one and two years before financial distress has a negative and no significant effect on financial distress probability, and the Non-Performing Loan from three years prior to financial distress have a significant negative and positive impact on financial distress probability.